2010
DOI: 10.1128/jvi.01416-09
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 Infection Activates the Unfolded Protein Response and Induces Apoptosis through Downregulation of p58 IPK and Activation of CHOP and SREBP1

Abstract: Cardiomyocyte apoptosis is a hallmark of coxsackievirus B3 (CVB3)-induced myocarditis. We used cardiomyocytes and HeLa cells to explore the cellular response to CVB3 infection, with a focus on pathways leading to apoptosis. CVB3 infection triggered endoplasmic reticulum (ER) stress and differentially regulated the three arms of the unfolded protein response (UPR) initiated by the proximal ER stress sensors ATF6a (activating transcription factor 6a), IRE1-XBP1 (X box binding protein 1), and PERK (PKR-like ER pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 67 publications
5
90
2
Order By: Relevance
“…118,119 Other DNA and RNA oncolytic viruses have been reported to induce apoptotic cancer cell death (Tables 4 and 5). However, there are only two reports showing that virus-induced ecto-CRT was correlated with enhanced intratumoral infiltrations of immune subpopulations, which accounted for the 'in vivo' remarkable antitumor immunity.…”
Section: Different Types Of Immunogenic Cancer Cell Death H Inoue Andmentioning
confidence: 99%
“…118,119 Other DNA and RNA oncolytic viruses have been reported to induce apoptotic cancer cell death (Tables 4 and 5). However, there are only two reports showing that virus-induced ecto-CRT was correlated with enhanced intratumoral infiltrations of immune subpopulations, which accounted for the 'in vivo' remarkable antitumor immunity.…”
Section: Different Types Of Immunogenic Cancer Cell Death H Inoue Andmentioning
confidence: 99%
“…For example, Hepatitis E virus (HEV) open reading frame 2 protein (ORF-2) is able to modulate ER stress induced apoptosis by increasing eIF2α phosphorylation and activation of CHOP, simultaneously (John, et al, 2011). Our lab also obtained a similar result in studying coxsackievirus B3 (CVB3)-induced apoptosis through phosphorylation of eIF2α and activation of CHOP; however, this activation is not through ATF4 but through ATF6 (Zhang, et al, 2010). For HEV, during infection, CHOP, which normally induces apoptosis and translocation of Bax to the mitochondria, is unable to perform this pro-apoptotic function.…”
Section: Viral Manipulation Of Er Stress Pathways and Componentsmentioning
confidence: 76%
“…It is known that apoptosis and necrosis both contribute to the cell death in myocarditis [3]; however, a change in degree of necrosis was not seen with miR-21 levels over the course of infection indicating the protection role of miR-21 in CVB3-induced myocarditis might depend on regulation of apoptosis. It has been reported that CVB3 infection can dramatically induce myocardial apoptosis via death receptor-mediated and mitochondrial-mediated signaling pathways [28][29][30], and apoptosis is also o en evidenced in patients of acute myocarditis [31]. Additionally, anti-apoptosis approaches signi cantly improved CVB3-induced heart injury [32,33], further con rming the pathological role of apoptosis in the acute myocarditis.…”
Section: Discussionmentioning
confidence: 86%